Analytical evaluation of compressive strength for concrete with rubber fine aggregates and the predictive model. (22nd August 2022) - Chen, Aijiu; Han, Xiaoyan; Wang, Zhihao; Zhang, Qing; Xia, Xiaozhou; Ji, Yanting; Li, Keliang
Highlights: The f cc of concrete with rubber aggregates of different sizes, contents and pretreatment methods were studied. Effects of rubber aggregates on the concrete mesostructure and the influence mechanism on f cc were clarified. A forecast model of rubberized concrete f cc at 28 days was proposed in this paper. Abstract: Recycling scrap tires as alternatives to materials to produce rubberized concrete will facilitate environmental protection and considerable conservation of natural resources. The accurate prediction of compressive strength for rubberized concrete will promote their development and application. In order to predict the compressive strength of rubberized concrete further accuracy, the rubberized concrete with rubber fine aggregates of different sizes, contents and pretreatment methods in compressive strength of 16.5–34.3 MPa were designed in this paper, and their cubic compressive strength was studied. Then, effects of the rubber aggregates on concrete mesostructure and the influence mechanism on compressive strength were analyzed through the technology of computed tomography and scanning electron microscope, as well as analyses of void structure of hardened concrete. The regularity of the varying cubic compressive strength of rubberized concrete with changing rubber size, content and the pretreatment method was clarified. The influence mechanism of the rubber on concrete compressive strength was revealed. Finally, a forecast model of cubic compressive strength for rubberized concrete with a good predictive ability was proposed, which can provide good references for design and engineering application of rubberized concrete.